Challenges to quantifying glass eel abundance from large and dynamic estuaries. (23rd September 2017) - Walmsley, Sarah; Bremner, Julie; Walker, Alan; Barry, Jon; Maxwell, David
Abstract: European eel Anguilla anguilla recruitment into the rivers of the northeastern Atlantic has declined substantially since the 1980s. Monitoring of recruiting juveniles, or glass eels, is usually undertaken in small estuaries and rivers. Sampling of large-scale estuaries is rare, due to the size of the sampling area and the resources needed to provide adequate sampling levels. Here we describe surveys for glass eels in the UK's largest estuarine system, the Severn Estuary/Bristol Channel. We sampled across a 20 km-wide stretch of the estuary in 2012 and 2013, using a small-meshed net deployed from a commercial fishing trawler, and the surveys yielded over 2500 glass eels. Eels were more abundant in the surface layer (0–1.4 m depth) than at depth (down to 8.4 m depth), were more abundant close to the south shore than along the north shore or middle of the estuary, and were more abundant in lower salinity water. Numbers were higher in the second year than in the first and eels were more abundant in February than April. The difficulties and logistics of sampling in such a large estuary are discussed, along with the level of resources required to provide robust estimates of glass eel abundance.